Correction: In vitro and in vivo burn healing study of standardized propolis: Unveiling its antibacterial, antioxidant and anti-inflammatory actions in relation to its phytochemical profiling. - Dina M El-Kersh; Rania F Abou El-Ezz; Eman Ramadan; Reham F El-Kased (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0302795.].